Sox2 is involved in paclitaxel resistance of the prostate cancer cell line PC-3 via the PI3K/Akt pathway - LI, DONG; ZHAO, LI-NAN; ZHENG, XIU-LAN; LIN, PING; LIN, FENG; LI, YUE; ZOU, HAI-FENG; CUI, RONG-JUN; CHEN, HUI; YU, XIAO-GUANG (Molecular medicine reports, 2014)
Prostate cancer is the most commonly diagnosed type of cancer and the second leading cause of cancer-associated mortality in males. The efficacy of prostate cancer chemotherapy is frequently impaired by drug resistance; however, the underlying mechanisms of this resistance remain elusive. Sex determining region Y-box 2 (Sox2) is of vital importance in the regulation of stem cell proliferation and carcinogenesis. In the present study, using MTT, clone formation, cell cycle and apoptosis assays, over-expression of Sox2 was demonstrated to enhance the paclitaxel (Pac) resistance of the PC-3 prostate cancer cell line, promoting cell proliferation and exhibiting an anti-apoptotic effect. Western blot analysis revealed that the phosphoinositide 3-kinase/Akt signaling pathway was activated in cells overexpressing Sox2, and by targeting cyclin E and survivin, Sox2 promoted G1/S phase transition and prevented apoptosis under Pac treatment. The present study provided an understanding of Pac resistance in prostate cancer and may indicate novel therapeutic methods for chemoresistant prostate cancer.